Funkční hodnocení fibrilace síní vypracované Kanadskou kardiovaskulární společností - Dorian, Paul (Clinical Cardiology Alert, 2009)
Atrial fibrillation (AF) is commonly associated with impaired quality of life. There is no simple validated scale to quantify the functional illness burden of AF. The Canadian Cardiovascular Society Severity in Atrial Fibrillation (CCS-SAF) scale is a bedside scale that ranges from class 0 to 4, from no effect on functional quality of life to a severe effect on life quality. This study was performed to validate the scale. METHODS AND RESULTS: In 484 patients with documented AF (62.2+/-12.5 years of age, 67% men; 62% paroxysmal and 38% persistent/permanent), the SAF class was assessed and 2 validated quality-of-life questionnaires were administered: the SF-36 generic scale and the disease-specific AFSS (University of Toronto Atrial Fibrillation Severity Scale). There is a significant linear graded correlation between the SAF class and measures of symptom severity, physical and emotional components of quality of life, general well-being, and health care consumption related to AF. Patients with SAF class 0 had age- and sex-standardized SF-36 scores of 0.15+/-0.16 and -0.04+/-0.31 (SD units), that is, units away from the mean population score for the mental and physical summary scores, respectively. For each unit increase in SAF class, there is a 0.36 and 0.40 SD unit decrease in the SF-36 score for the physical and mental components. As the SAF class increases from 0 to 4, the symptom severity score (range, 0 to 35) increases from 4.2+/-5.0 to 18.4+/-7.8 (P<0.0001). CONCLUSIONS: The CCS-SAF scale is a simple semiquantitative scale that closely approximates patient-reported subjective measures of quality of life in AF and may be practical for clinical use.
Keywords: průzkumy a dotazníky; Female; Atrial Fibrillation; Age Factors; multivariační analýza; Quality of Life; Validation Studies as Topic; ženské pohlaví; Kanada; Surveys and Questionnaires; Multivariate Analysis; urgentní zdravotnické služby; Reproducibility of Results; kvalita života; věkové faktory; Health Status; validační studie jako téma; zdravotní stav; lidé; Emergency Medical Services; stupeň závažnosti nemoci; hospitalizace; Sex Factors; reprodukovatelnost výsledků; Canada; Male; Aged; sexuální faktory; Hospitalization; fibrilace síní; lidé středního věku; senioři; mužské pohlaví; Severity of Illness Index; Middle Aged; Humans